Microfinance and the Fight Against Poverty in the Democratic Republic of Congo - Kibatshi, Marcel Kamba (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2018)
Studying both the Congolese and Cameroonian cases, this article shows that beyond some normalisation, microfinance prompts some very distinctive ways of appropriation. The authors wonder about the role of states as “ferrymen” of the word “microfinance”. They question the ability and the freedom of organisations and local authorities to put in place microfinance schemes. In a first section, the paper underlines the normative conception going with the term “microfinance”. In a second and third sections it discusses the circulation of the term and the manufacture of practices in the Democratic Republic of Congo and Cameroon. It comes to the conclusion that despite the eventual enforcement of practices and social norms, microfinance has to acclimatize itself to divergent social, political and even religious practices.